Cơ chế chuyển hóa từ nhận thức lợi ích đến hành vi du lịch tái tạo: Vai trò điều tiết của các yếu tố môi trường - Trịnh Văn , Thảo; Lê Chí , Công (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study clarifies the mechanism through which perceived economic, social, and environmental benefits influence international tourists’ regenerative tourism behavior in Khanh Hoa Province. It also examines the moderating roles of perceptions of nature-based solutions, perceived natural authenticity, and environmental concern in the attitude - behavior relationship. Drawing on an integrated framework combining the Value-Belief-Norm theory (VBN), the Theory of Planned Behavior (TPB), and the Value-Attitude-Behavior model (VAB), this study develops and tests a theoretical framework using PLS-SEM. to evaluate the measurement model and test the proposed hypotheses. The findings reveal that all three dimensions of perceived benefits positively influence attitude, with economic benefits demonstrating the strongest effect. Attitude serves as a mediating factor, while the moderating variables strengthen the positive effect of attitude on behavior. These findings provide empirical evidence and managerial implications for policymaking on regenerative tourism development at the destination level